The Problem of Preschoolers' Dance Creativity in Modern Foreign Studies - E.V. Gorshkova (Современная зарубежная психология)
The article examines modern foreign studies of the problem of dance creativity of children 3—7 years, carried out by authors from different countries (Australia, Great Britain, Israel, China, Mexico, USA, Turkey, Finland, Switzerland, etc.); identifies existing psychological and pedagogical approaches to solving this problem abroad; compares the content of these studies with some Russian approaches to this problem. On this basis, the hypothesis of the difference in solving this problem in Russia and abroad is tested. The definitions of a number of concepts are preliminarily considered: motor image, dance image, language of movements (in dance), etc., which reflect how researchers understand the essence of creativity in dance, which affects the search for ways and conditions of its development in modern 3—7 year olds. Based on the comparison, it was found that foreign studies are more concerned with the problem of integrating children's creative dance into the education system on an ongoing basis in order to promote their self-expression in movement to music, seeing it as a means of their personal development, increasing their motivation in learning. In domestic studies (for preschoolers), the emphasis is on identifying the features of the activity itself the creativity of children in dance.